Bentuk Penyajian Dikia Rabano dalam Acara Jopuik Antau Marapulai di Nagari Lubuak Alai Kecamatan Kapur IX Kabupaten Lima Puluh Kota - Dedek Febrian; Yensharti Yensharti (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This study aims to find out and describe the form of presentation of Dikia Rabano by the "Tukang Dikiu" group in the Jopuik Antau Marapulai event in Lubuak Alai, Kapur IX District, Lima Puluh Kota Regency. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the existence of Dikia Rabano art in Nagari Lubuak Alai is still appreciated and continues to this day. Dikia Rabano's art is able to influence society and become a symbol of a community such as the niniak mamak procession on Islamic holidays and bridal processions. The form of Dikia Rabano's presentation in Nagari Lubuak Alai is played by standing while walking along the procession of niniak mamak and bridal rows. The song sung in Dikia Rabano is a verse with Islamic nuances, in ancient times this song was believed to be a song of a mother in putting her child to sleep.